The Role of Fluoxetine in Activating Wnt/β-Catenin Signaling and Repressing β-Amyloid Production in an Alzheimer Mouse Model - Huang, Min; Liang, Yubin; Chen, Hongda; Xu, Binchu; Chai, Cuicui; Xing, Pengfei (Frontiers in Aging Neuroscience, 2018)
Fluoxetine (FLX) is one of the selective serotonin reuptake inhibitors (SSRIs) antidepressants, which could be used to relieve depression and anxiety among AD patients. This study was designed to search for new mechanisms by which fluoxetine could activate Wnt/β-catenin signaling pathway and reduce amyloidosis in AD brain. Fluoxetine was administered via intragastric injection to APP/tau/PS1 mouse model of Alzheimer’s disease (3×Tg-AD) mice for 4 months. In the hippocampus of AD mouse model, there could be observed neuronal apoptosis, as well as an increase in Aβ (amyloid-β) production. Moreover, there is a strong association between down-regulation of Wnt/β-catenin signaling and the alteration of AD pathology. The activity of protein phosphatases of type 2A (PP2A) could be significantly enhanced by the treatment of fluoxetine. The activation of PP2A, caused by fluoxetine, could then play a positive role in raising the level of active β-catenin, and deliver a negative impact in GSK3β activity in the hippocampal tissue. Both the changes mentioned above would lead to the activation of Wnt/β-catenin signaling. Meanwhile, fluoxetine treatment would reduce APP cleavage and Aβ generation. It could also prevent apoptosis in 3×Tg-AD primary neuronal cell, and have protective effects on neuron synapse. These findings imply that Wnt/β-catenin signaling could be a potential target outcome for AD prevention, and fluoxetine has the potential to be a promising drug in both AD prevention and treatment.